2013
DOI: 10.1371/journal.pone.0069583
|View full text |Cite|
|
Sign up to set email alerts
|

PrPST, a Soluble, Protease Resistant and Truncated PrP Form Features in the Pathogenesis of a Genetic Prion Disease

Abstract: While the conversion of PrPC into PrPSc in the transmissible form of prion disease requires a preexisting PrPSc seed, in genetic prion disease accumulation of disease related PrP could be associated with biochemical and metabolic modifications resulting from the designated PrP mutation. To investigate this possibility, we looked into the time related changes of PrP proteins in the brains of TgMHu2ME199K/wt mice, a line modeling for heterozygous genetic prion disease linked to the E200K PrP mutation. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In contrast to the mitigating effect on sleep abnormalities, co-expression of WT PrP does not significantly modify the time of onset and progression of motor dysfunction or prolong survival of Tg(FFI) mice, consistent with the dominant mode of inheritance of FFI and with similar observations in other mutant PrP mice [ 14 , 19 , 43 ]. Thus, WT PrP influences only some aspects of the Tg(FFI) phenotype, perhaps those that are more dependent on a physiological function of PrP in neuronal excitability [ 44 ].…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to the mitigating effect on sleep abnormalities, co-expression of WT PrP does not significantly modify the time of onset and progression of motor dysfunction or prolong survival of Tg(FFI) mice, consistent with the dominant mode of inheritance of FFI and with similar observations in other mutant PrP mice [ 14 , 19 , 43 ]. Thus, WT PrP influences only some aspects of the Tg(FFI) phenotype, perhaps those that are more dependent on a physiological function of PrP in neuronal excitability [ 44 ].…”
Section: Discussionsupporting
confidence: 80%
“…Insertion of the E to K mutation at the relevant position (codon 199, representing the human E200K mutation) led to the generation of a transgenic mouse line (TgMHu2ME199K/KO). These mice suffer from progressive neurological symptoms as early as 5–6 month of age and deteriorate to a terminal condition several months thereafter, concomitant with the accumulation of a truncated form of protein kinase-resistant PrP (Kovacs et al, 2010; Friedman-Levi et al, 2011, 2013). TgMHu2ME199K/KO mice exhibit typical pathological features of human CJD, such as gliosis and lipid oxidation, and have already been used successfully to test the activity of a candidate reagent (Mizrahi et al, 2014)…”
Section: Tgmhu2me199k/ko: a Transgenic Mouse Model Of Familial Prion mentioning
confidence: 99%
“…Sweeting et al (2013) produced X-ray structures of mutants in the β2-α2 loop and reported that the helix-capping motif in the β2-α2 loop modulates β-state misfolding in RaPrP, and still acknowledged "rabbit PrP, a resistant species" (Sweeting et al (2013)). Friedman- Levi et al (2013) reported "pAb RTC and EP1802Y (EP), a rabbit α PrP mAb directed against the CITQYER ESQAYYQRGS sequence present at the C-terminal part of human PrP, just before the PrP GPI anchor" (Friedman-Levi et al (2013)). Timmes et al (2013) used R20 as the rabbit polyclonal anti-PrP antibody (Timmes et al (2013)).…”
Section: A Detailed Review On Rabbit Prpmentioning
confidence: 99%